Synthesis and Characterization of New Schiff Bases Derived from Reaction of The Cefixime with Benzaldehyde Derivatives and Evaluation of Their Biological Activity - Salwaa A. S. Jabbar; Mahmood M. Mahmood (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The Schiff bases (1-10) were synthesized by the reaction of cefixime  with aldehydes derivatives. The characterization of Schiff bases were carried out, by using   spectroscopic techniques including IR, U.V â€“ Vis, H1-NMR, EI-MS along with elemental analyses (C.H.N.).